Lessons learned from nursing crisis meetings: Qualitative study to evaluate nurses' experiences and needs - Sabine Adriana Johanna Josepha op 't Hoog; Annemarie Johanna Burgje Maria de Vos (Wiley, 2024)
Abstract Aims The aim of this study is to evaluate the nurses' experiences with the Nursing Crisis Meetings and to identify nurses' needs regarding the future governance structure. Design Qualitative study. Methods Two focus groups were conducted in February 2022 with participants of the Nursing Crisis Meetings (N = 15). We used thematic analysis to describe themes. Results We identified five themes: opportunity to speak up, call for nursing leadership, call for control over practice and autonomy, development of a governance infrastructure and development of the professional nurse role. Conclusion Nurses experienced the Nursing Crisis Meetings to be a positive and empowering infrastructure, which facilitates the unique opportunity to speak up and share experiences and concerns. This new infrastructure is a promising strategy to engage nurses during a pandemic and to build on a professional governance structure. Impact This paper highlights the need for nurses to speak up and be engaged during the COVID‐19 pandemic and gives a practical example of how to put this infrastructure into practice.